Persepsi Kemudahan, Persepsi Manfaat, dan Persepsi Kepercayaan terhadap Minat Menggunakan Fitur Robo Advisor pada Aplikasi Bibit Oleh Investor Pemula di Indonesia - Muchammad Haikal Akbar Winarko; Achmad kautsar; Achmad Fitro; Dhiyan Septa Wihara (CV. AFDIFAL MAJU BERKAH, 2026)
The development of financial technology has increased the use of artificial intelligence-based digital investment services, including the Robo-Advisor feature in the Bibit application. This study aims to analyze the influence of Perceived Ease of Use (PEOU), Perceived Usefulness (PU), and Perceived Trust (PT) on Behavioral Intention (BI) to use the Robo-Advisor feature on the Bibit application. This study employed a quantitative approach using purposive sampling involving 203 respondents who were novice investors and users of the Bibit application in Indonesia. Data were collected through an online questionnaire and analyzed using multiple linear regression with IBM SPSS Statistics 26. The results show that Perceived Ease of Use has no significant effect on Behavioral Intention (p = 0.097 > 0.05), while Perceived Usefulness (p = 0.000 < 0.05) and Perceived Trust (p = 0.002 < 0.05) have positive and significant effects on Behavioral Intention. Simultaneously, Perceived Ease of Use, Perceived Usefulness, and Perceived Trust have a significant effect on Behavioral Intention, as indicated by F = 129.554 with p = 0.000. The regression model has an Adjusted R² of 0.656, indicating that the three independent variables explain 65.6% of the variance in Behavioral Intention, while the remaining 34.4% is explained by other factors outside the research model. These findings indicate that perceived usefulness and perceived trust are more important factors than perceived ease of use in influencing users’ intention to use the Robo-Advisor feature on the Bibit application